2021
DOI: 10.21273/jashs05019-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fruit Bagging on Anthocyanin Accumulation and Related Gene Expression in Peach

Abstract: Fruit bagging is a popular agricultural practice that has been widely used to physically protect fruit. However, the application of fruit bags usually has various effects on fruit quality. In this study, three kinds of paper bags with different colors and transmittance were applied to investigate their effects on the skin coloration and related gene expression of peach (Prunus persica). Our findings showed that bagging treatment inhibited anthocyanin accumulation and the expression of related structural and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…In this study, our findings demonstrated that bagging treatment significantly increased anthocyanin accumulation, reduced chlorophyll content, and promoted the expression level of anthocyanin synthesis genes in the inner pericarp of 'Hongyang' kiwifruit, which is in accordance with the previous studies on kiwifruit [39], apple [40] and peach [41]. However, despite being reported as a light-responsive and versatile transcription factor that directly binds to, and induces, the expression of certain MYB transcription factors, or that activates the expression of biosynthetic enzyme genes in conjunction with PIF3 activity along with other MYB factors [24,[42][43][44][45], HY5 did not demonstrate any significant synergistic effect on fruit-bagging-induced anthocyanin synthesis in 'Hongyang'.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, our findings demonstrated that bagging treatment significantly increased anthocyanin accumulation, reduced chlorophyll content, and promoted the expression level of anthocyanin synthesis genes in the inner pericarp of 'Hongyang' kiwifruit, which is in accordance with the previous studies on kiwifruit [39], apple [40] and peach [41]. However, despite being reported as a light-responsive and versatile transcription factor that directly binds to, and induces, the expression of certain MYB transcription factors, or that activates the expression of biosynthetic enzyme genes in conjunction with PIF3 activity along with other MYB factors [24,[42][43][44][45], HY5 did not demonstrate any significant synergistic effect on fruit-bagging-induced anthocyanin synthesis in 'Hongyang'.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, our findings demonstrated that bagging treatment significantly increased anthocyanin accumulation, reduced chlorophyll content, and promoted the expression level of anthocyanin synthesis genes in the inner pericarp of 'Hongyang' kiwifruit, which is in accordance with the previous studies on kiwifruit [39], apple [40] and peach [41]. However, despite being reported as a light-responsive and versatile transcription factor that directly binds to, and induces, the expression of certain MYB transcription…”
Section: Discussionsupporting
confidence: 92%
“…The expressions of four of the structural biosynthetic pathway genes ( CHS , F3H , DFR , and UFGT ) were significantly repressed by bagging. The expression of MYB10.1 was also suppressed by fruit bagging and closely paralleled the changes that occurred in anthocyanin content, which might suggest that MYB10.1 has a major role in the light‐mediated regulation of anthocyanin biosynthesis in the pericarp of peach (Y. Ma, Zhao, et al., 2021).…”
Section: The Impacts Of Light On Anthocyanin Contentmentioning
confidence: 82%
“…Horbowicz et al (86) have also reported the considerable variation in anthocyanin content of the fruits among different species or cultivars within the same species. This difference in anthocyanin content among these fruits might be due to the effects of genetics, agro-ecological conditions such as pH, light, temperature, and horticultural practices (91). In our study, it was also observed that the fruits with higher anthocyanin content, such as H. Validus (−0.7 ± 0.71) and P. nepalensis (−0.1 ± 1.22) had the lowest b * value (Table 5).…”
Section: Total Monomeric Anthocyanin Contentmentioning
confidence: 99%